The Role of The Village Government in Gender-Based Community Empowerment in Curuglanglang Village, Munjul Pandeglang District - Ariyan, Said; Mardiah, Dedeh (Lenggogeni Data Publishing, 2025)
This study aims to analyze the role of village government in gender-based community empowerment in Curuglanglang Village, Munjul District, Pandeglang Regency. Gender inequality remains a significant issue at the village level, where women's participation in development is still limited. The research applies the Harvard Gender Analysis Model focusing on four key components to understand gender roles and relations within the community. This study employs a descriptive qualitative method by conducting in-depth interviews with nine informants from various community groups, and data validity was tested through triangulation. The findings indicate that the village government’s role in gender-based community empowerment is still suboptimal. The low participation of women in development activities and the lack of public awareness regarding gender equality are major obstacles. The village government is expected to formulate more gender-responsive policies and programs, and to enhance education and public awareness of women’s vital role in village development.